2010
DOI: 10.3944/aott.2010.2275
|View full text |Cite
|
Sign up to set email alerts
|

Locking plate fixation of three- and four-part proximal humeral fractures

Abstract: Preservation of humeral head vascularity through minimal soft tissue dissection, fixation with a locking plate, and early postoperative motion were effective in decreasing potential complications following surgical treatment of three- and four-part proximal humeral fractures. The degree of fracture comminution and age of the patients affect functional results significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
2
12
1
3
Order By: Relevance
“…The final follow up mean Constant Score was found to be 82.79. The above results are comparable with results in literature, Resch et al [10] , Francesco et al [11] , Fenichel et al [12] , emphasizing the fact that minimally invasive fixation procedure can deliver best results and optimal functional outcome with least damage to soft tissue anatomy. Out of 10 patients treated by Open Reduction and Internal Fixation with anatomical locking plate, 3 (30%) had excellent outcome, 4 (40%) had good outcome, 2 (20%) patients had fair outcome and 1 (10%) had poor outcome.…”
Section: Discussionsupporting
confidence: 82%
“…The final follow up mean Constant Score was found to be 82.79. The above results are comparable with results in literature, Resch et al [10] , Francesco et al [11] , Fenichel et al [12] , emphasizing the fact that minimally invasive fixation procedure can deliver best results and optimal functional outcome with least damage to soft tissue anatomy. Out of 10 patients treated by Open Reduction and Internal Fixation with anatomical locking plate, 3 (30%) had excellent outcome, 4 (40%) had good outcome, 2 (20%) patients had fair outcome and 1 (10%) had poor outcome.…”
Section: Discussionsupporting
confidence: 82%
“…Bazı yazarlar standart deltopektoral yaklaşımı tercih ederken [14][15][16][17] diğerleri ise, bu yaklaşımın humerus başının vasküla-rizasyonunda önemli bir role sahip olan anterior sirkumfleks arterin yaralanmasına neden olabileceği gerekçesiyle deltoid split yaklaşımı tavsiye etmektedir. [11,18] Proksimal humerusun 270 derece kontrolüne, kırığın tipine ve yer değiştirmesine göre gerektiğinde tip C kırıklarda artiküler redüksiyonu kolaylaştırmak için döndürücü manşet longitüdinal olarak açılır. Tüberküler fragmanlardan ve döndürücü manşet tendonlarından geçirilen 5 numara Ethibond dikişlerle redüksiyon ve kemik fragmanlarının plağa tespitine olanak sağ-lanır.…”
Section: Discussionunclassified
“…Three Part Four Part Our study 8 27 10 Geiger et al, [18] 8 12 4 Erasmo et al, [25] 7 40 35 Parmaksizoglu et al, [19] -12 20 Kumar et al, [20] 8 15 23 Chowdary et al, [23] 22 38 10 Hitesh et al, [27] 10 14 6…”
Section: Neer Fracture Pattern Two Partmentioning
confidence: 99%
“…Geiger et al, [18] Parmarksizoglu et al, [19] Kumar GN et al, [20] Korkmaz et al, [21] Kilic et al, [22] Chowdary et al, [23] Aksu et al, [24] Hitesh et al, [27] Our Study Male 8 10 35 16 13 54 33 7 15 Female 20 22 16 25 9 16 70 23 30 Thus, in our study two thirds of the patients were females, which presents the ratio of 2:1 similar to those studies reported by Parmaksizoglu et al, Aksu et al, Hitesh et al and Geiger et al This confirms our earlier comment that this pattern of fracture occurring in the elderly are more commonly seen in the elderly women, more so about the age of 60 years.…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation